Service Quality and Consumer Purchase Intention: A Correlational Study of Institutional Services - Kurniawan, Asep; Suwandi; Budiarti, Erika Mei; Fatih, Muhammad Al; Seno Aji, Tony (Al-Qalam Institue, 2025)
This study aims to examine the relationship between the service quality of educational institutions and consumers’ purchase intentions. The research is motivated by the growing importance of institutional quality in maintaining the competitiveness and sustainability of educational institutions in an era of rapid change. A quantitative research design was employed using a simple correlation analysis to identify the degree of association between the two variables. The study involved 100 respondents, consisting of parents of students, selected through a cluster sampling technique from four regions where the elementary schools are located. Data were collected through a structured questionnaire, and the results of the item analysis indicated that all questionnaire items demonstrated high validity and reliability. These findings suggest that the data are highly credible and that the conclusions drawn from the analysis are reliable. The results of the correlation analysis revealed a significant positive relationship between service quality and purchase intention. This implies that the higher the perceived quality of services provided by the educational institution, the greater the consumers’ willingness to enroll or recommend the institution.